2019
DOI: 10.3390/coatings9060372
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Fabrication of Chemical Solution-Deposited Lanthanum Nickelate Thin Films via Intense Pulsed-Light Process

Abstract: In this paper, we demonstrate the practicality and feasibility of the flash light-sintering method to fabricate the ceramic material perovskite structure for lanthanum nickel oxide (LaNiO3; LNO) thin films using flash light irradiation equipment. LNO thin films are deposited on an Si wafer and Al2O3 substrate via the chemical solution deposition (CSD) method and sintered by a thermal and flash light-irradiation process with a bottom heater. The properties of flash light-sintered LNO thin films are compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“… Electrical resistivity of LNO with various internal structures. Values of the resistivity marked with numbers 1–18 are taken from the following references: 1—[ 88 ], 2—[ 89 ], 3—[ 28 ], 4—[ 92 ], 5—[ 30 ], 6—[ 20 ], 7—[ 90 ], 8—[ 30 ], 9—[ 90 ], 10—[ 29 ], 11—[ 27 ], 12—[ 22 ], 13—[ 15 ], 14—[ 42 ], 15—[ 19 ], 16—[ 41 ], 17—[ 22 ], 18—[ 19 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“… Electrical resistivity of LNO with various internal structures. Values of the resistivity marked with numbers 1–18 are taken from the following references: 1—[ 88 ], 2—[ 89 ], 3—[ 28 ], 4—[ 92 ], 5—[ 30 ], 6—[ 20 ], 7—[ 90 ], 8—[ 30 ], 9—[ 90 ], 10—[ 29 ], 11—[ 27 ], 12—[ 22 ], 13—[ 15 ], 14—[ 42 ], 15—[ 19 ], 16—[ 41 ], 17—[ 22 ], 18—[ 19 ]. …”
Section: Figurementioning
confidence: 99%
“…However, columnar grain growth in LNO films is challenging. Most of the authors who studied the CSD of LNO films on substrates of various structures reported films with a porous, polycrystalline structure and fine equiaxed grains [ 19 , 24 , 41 , 42 ]. The defective structure causes enhanced resistivity, and it is not optimal for growing on the ferroelectric perovskite layer or other functional heterostructures [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be improved by adding a pretreatment process or a heater. IPL sintered perovskitestructured lanthanum nickel oxide (LaNiO 3 ; LNO) thin films was demonstrated [114]. To prove electrical properties of LNO IPL sintering, the authors performed the IPL process on plate-heater of 500 °C.…”
Section: Sintering Of Metal Oxide Nanostructuresmentioning
confidence: 99%
“…The end-member of the series LaNiO 3 (LNO) with a rhombohedral crystallographic structure exhibits the metallic conductivity at all temperatures. Low conductivity and superior catalytic properties make LNO attractive for use as functional sublayers in perovskite heterostructures [1]. Other nickelates with the orthorhombic structure display a sharp metal-to-insulator transition (MIT) from a hightemperature paramagnetic metal state to a low-temperature antiferromagnetic insulator.…”
Section: Introductionmentioning
confidence: 99%